2018
DOI: 10.1002/jhet.3085
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of N‐Substituted Condensed Tetrahydropyridine‐Based Enaminones via Palladium‐Catalyzed Intramolecular C–N Cross‐coupling

Abstract: A number of β‐enaminones with secondary amino group (alkyl, cyclopropyl, and aryl) were prepared from corresponding β‐diketones. Two general protocols for their palladium‐catalyzed intramolecular C–N cross‐coupling were established to give corresponding N‐substituted condensed tetrahydropyridines in good yields. The methodology is applicable for a wide variety of structural motifs. The work also extends the applicability of novel, recently established, palladium precatalysts to new substrates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Since the Claisen condensation is accompanied by formation of side products, purification of a diketone is usually difficult. Steam distillation of the reaction mixture followed by precipitation of metal (Cu, Mg, Mn, Fe) chelates and their acidic decomposition [2223] or preparative chromatography [3334] were used to obtain a pure product. We have found that in most cases, simple vacuum distillation of the crude reaction mixture is sufficient to obtain pure β-diketones with fluorinated side-chain.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the Claisen condensation is accompanied by formation of side products, purification of a diketone is usually difficult. Steam distillation of the reaction mixture followed by precipitation of metal (Cu, Mg, Mn, Fe) chelates and their acidic decomposition [2223] or preparative chromatography [3334] were used to obtain a pure product. We have found that in most cases, simple vacuum distillation of the crude reaction mixture is sufficient to obtain pure β-diketones with fluorinated side-chain.…”
Section: Resultsmentioning
confidence: 99%
“…Several methods for decomposition of copper chelates were described in literature. Usually sulfuric acid with various concentrations (10–95%) was applied [2223 3435], but the thiophene ring is known to be sensitive to sulfuric acid. For this reason, we developed two new mild protocols for the regeneration of diketones (Scheme 3).…”
Section: Resultsmentioning
confidence: 99%
“…(R)-(1,1'-binaphthyl)-2,2'-diylbis(trifluoromethanesulfonate) was prepared from (R)-BINOL (Fluorochem) using the published method [14]. (±)-2,2'-Bis(bromomethyl)-1,1'-binaphthyl 2 was prepared [4] by NBS bromination of (±)-2,2'-dimethyl-1,1'-binaphthyl, itself obtained by Grignard mediated coupling [5] of 1-bromo-2-methylnaphthalene [15].…”
Section: Methodsmentioning
confidence: 99%